FAUNA TANAH PADA STRATIFIKASI LAPISAN TANAH BEKAS PENAMBANGAN EMAS DI JAMPANG, SUKABUMI SELATAN - Erniwati - Erniwati (Masyarakat Zoologi Indonesia, 2008)
Erniwati. 2008. Soil fauna of soil layer stratifications in the ex-gold mining area inJampang, Sukabumi Selatan . Zoo Indonesia 17(2): 83-91. Study on the diversity ofsoil fauna was conducted in the degraded area post gold mining at Jampang, SouthSukabumi, West Java. Soil fauna samples were collected from two plots of 20 x 10 mwhich were established randomly within one hectare area. Each plot was divided into20 subplots at 2 x 5 m in size. Soil samples were taken by digging to pits alternatelyamong the 20 subplots. In each subplots, soil collection was conducted at 5 cm intervalwith the size 20 x 20 x 25 cm (length x width x depth) until 25 cm in depth and collectedon separate cotton bags. Arthropods and other fauna were collected by aspirator or byhand and preserved in vials containing 96% ethanol. A total of 1584 individuals of soilfauna were collected from the two locations, represented by 14 families, 9 orders, and8 classes. Soil fauna being found were Gryllidae, Blattidae, Isoptera, Formicidae,Arachnida, Gastropoda, Collembola, Oligochaeta, and others Arthropoda. The dominanttaxa was ants (Formicidae) and earth worms (Oligochaeta).